2009
DOI: 10.1242/jeb.024455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a short period of elevated circulating corticosterone on postnatal growth in free-living Eurasian kestrelsFalco tinnunculus

Abstract: SUMMARYEnvironmental conditions affect growth and development and, through developmental plasticity, create phenotypic variation. In suboptimal conditions current survival is traded-off against development. Corticosterone, the main glucocorticoid in birds, may be involved in the reallocation of energy from growth to maintenance, but its effect on growth has rarely been investigated in altricial birds under natural conditions in the wild. In free-living Eurasian kestrel Falco tinnunculus nestlings, we artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 50 publications
12
52
1
Order By: Relevance
“…For example, fledgling Magellanic Penguins (Spheniscus magellanicus) showed no difference in baseline or stress-induced CORT across tourist and non-tourist visited areas [51] and Black-legged Kittiwake chicks (Rissa tridactyla) did not differ in their baseline or stress-induced CORT across levels of investigator disturbance [7]. R epeated exposure to stressors may have severe negative consequences on developing young such as suppression of growth [29] and reduced cognition [21] and even influence the probability of survival [4]. Thus the ability to maintain low baseline and stress-induced CORT in the face of environmental perturbations may act to minimize the deleterious effects of CORT on developing kestrels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fledgling Magellanic Penguins (Spheniscus magellanicus) showed no difference in baseline or stress-induced CORT across tourist and non-tourist visited areas [51] and Black-legged Kittiwake chicks (Rissa tridactyla) did not differ in their baseline or stress-induced CORT across levels of investigator disturbance [7]. R epeated exposure to stressors may have severe negative consequences on developing young such as suppression of growth [29] and reduced cognition [21] and even influence the probability of survival [4]. Thus the ability to maintain low baseline and stress-induced CORT in the face of environmental perturbations may act to minimize the deleterious effects of CORT on developing kestrels.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of DEX were also more transient because changes in morphometrics from day 7 to day 11 of DEX-treated birds did not differ from those of placebo birds, suggesting compensatory growth (Müller et al, 2009b). We used the DEX treatment to induce negative feedback in the HPA (Westerhof et al, 1994) and expected decreased plasma CORT and CORT f , but these variables did not differ significantly between DEX and control birds, and birds in the CORT+DEX group were statistically similar to birds in the CORT group.…”
Section: Discussionmentioning
confidence: 99%
“…This result was unexpected as stressful experiences often depress growth in the short-term (Eriksen et al, 2003;Hayward and Wingfield, 2004;Saino et al, 2005;Janczak et al, 2006;Spencer and Verhulst, 2007;Müller et al, 2009;Spencer et al, 2009). Studies of pre-natal stress have also suggested that males are more affected than females (Love et al, 2005;Hayward et al, 2006;Love and Williams, 2008).…”
Section: Pre-and Post-natal Effects Of Corticosterone On Growthmentioning
confidence: 97%